The dynamics and control of glycemia in the case of diabetes - Švitra, Donatas; Vilkytė, Ramunė (Lietuvos matematikos rinkinys, 2012)
In this article the authors performed of glycemic regulation mathematical model described one differential equation with delay argument and one algebraic equation linear, nonlinear and numeric analyses. Linear analysis was performed D-segmentation method. A stable periodic solution application on bifurcation theory was constructed in the nonlinear analysis. The numeric solutions of glycemia dynamics have been constructed in the numeric analysis of the diabetes case, introducing to the three external periodic functions determinating food, exogenous insulin injections (Lispro) and physical exercise. Glycemic dynamic was calculated applying program “Model Maker”.